The Theory Of The Value Determinism In The Media - لونيس ياديس (International Journal of Social Communication, 2014)
With the development of media and communication research among Western Researchers, it is clear that this type of research is living in an academic crisis at the level of Arab studies, where it is limited to some foreign projections that do not often collide with the specificities of the Arab society and in this context arguably the value imperative of Azzi It came as a theoretical work that corresponds to different social contexts.